Physiological Adaptations to Swimming in Fish - Leonardo J. Magnoni; Arjan P. Palstra; Josep V. Planas (Frontiers Media SA, 2017)
Swimming is an integral part of the life history of many fish species as is intimately linked with their ability to express feeding and predator avoidance behaviors, habitat selection and environmental preferences, social and reproductive behaviors as well as migratory behaviors. Therefore, swimming is an important determinant factor of fitness in a true Darwinian sense and, not surprisingly, swimming performance has been often used as a measure of physiological fitness in fish. The main aim of this Research Topic is to showcase some of the current studies designed to improve our understanding of the physiological energetic and metabolic requirements of swimming and of the adaptive responses to swimming in fish.
English
Keywords: swimming economy; performance; fish; swimming exercise; growth